Unleashing the Creativity and Innovation of Our Greatest Resource—The Governmental Public Health Workforce. (March 2019) - Locke, Rachel; Castrucci, Brian C.; Gambatese, Melissa; Sellers, Katie; Fraser, Michael
Abstract : Context: Creativity and innovation in the governmental public health workforce will be required to generate new ideas to solve complex problems that extend beyond traditional public health functions such as disease surveillance and monitoring. Creativity and innovation can promote and advance necessary organizational transformation as well as improve organizational culture and workplace environment by motivating employees intrinsically. However, there is little empirical evidence on how rewarding creativity and innovation in governmental public health departments is associated with organizational culture and workplace environments. Objective: This study describes (1) the degree to which creativity and innovation are rewarded in governmental public health agencies and (2) associations between rewarding creativity and innovation and worker satisfaction, intent to leave, and workplace characteristics. Design: The cross-sectional Public Health Workforce Interests and Needs Survey (PH WINS) was administered using a Web-based platform in fall 2017. Settings and Participants: Data used for these analyses were drawn from the 2017 PH WINS of governmental health department employees. This included state health agency and local health department staff. PH WINS included responses from 47 604 staff members, which reflected a 48% overall response rate. PH WINS excludes local health departments with fewer than 25 staff or serving fewer than 25 000 people. Results: Fewer than half of all workers, regardless of demographic group and work setting, reported that creativity and innovation were rewarded in their workplace. Most measures of worker satisfaction and workplace environment were significantly more positive for those who reported that creativity and innovation were rewarded in their workplace. Conclusion: This research suggests that promoting creativity and innovation in governmental public health agencies not only could help lead the transformation of governmental public health agencies but could also improve worker satisfaction and the workplace environment in governmental public health agencies.